Liderazgo educativo y su incidencia en el desarrollo del aprendizaje basado en proyectos, en la Unidad Educativa Tiopamba, 2023-2024 - Álvarez Jiménez, María Cenelia (2024)
The content of this research work analyzes educational leadership and the methodology of project-based learning. For the study of the two variables, a qualitative approach was used, with a descriptive and explanatory scope, it has a non-experimental design because the study variables were evaluated without changing the conditions. The inductive and analytical methods were used. With regard to obtaining the information, the survey technique was used, which was applied to a sample of 65 students and 15 teachers, the results of which made it possible to determine the type of leadership practiced by teachers and the impact on the application of project-based learning. Once the data was obtained, it was possible to conclude that there is a relationship between educational leadership and project-based learning; Teachers do not have practical methodological guidance that allows them to guide their work towards the use of project-based learning, which is a necessity for teachers. Once the study was completed, a proposal called “Working with PBL” was put together, which is aimed at working with upper elementary students, which will help improve the teaching-learning process, because currently teachers do not use this methodology due to ignorance.